Improving the Quality of Islamic Education through the Implementation of Integrated Quality Management - Reyhana Nur Azizah; Sofia Nisa Ulyantika; Melyna Wijaya Putri; Idham Kholid; Yuniar (Al-Qalam Institue, 2025)
The implementation of Total Quality Management (TQM) in Islamic education has become a crucial issue for improving service quality, learning, and institutional governance amid the challenges of globalization and the digital era. This study aims to explore the implementation of TQM in Islamic educational institutions and identify the barriers and their contribution to improving educational quality. The research method is a descriptive, qualitative approach, using in-depth interviews, participant observation, and document analysis across several Islamic schools and madrasas that have implemented TQM. The results show that although TQM has excellent potential to improve educational quality, its implementation is still hampered by a hierarchical organizational culture, a mismatch between modern managerial principles and Islamic educational culture, and limited infrastructure and human resources. This study concludes that to increase the effectiveness of TQM in Islamic education, there needs to be a more contextual and adaptive adjustment to the management model, as well as the strengthening of the integration of Islamic values across all managerial aspects. The contribution of this research is the development of a TQM model grounded more in Islamic moral and spiritual values.